The Textualization of Problem Handling: Lean Discourses Meet Professional Competence in Eldercare and the Manufacturing Industry. (July 2016) - Karlsson, Anna-Malin; Nikolaidou, Zoe
This article reports on research addressing the role of incident reporting at the workplace as a textual representation of lean management techniques. It draws on text and discourse analysis as well as on ethnographic data, including interviews, recorded interaction, and observations, from two projects on workplace literacy in Sweden: a study in an eldercare facility and a study in a large factory. Analysis of the data set demonstrates striking similarities, both in the way incident reporting texts are structured and worded and in the literacy practices that contextualize them. Dominant characteristics in the texts are the absence of actors and the structured, process-based approach of problems and problem handling. The forms often generate conflicts in the ways workers are asked to textually represent an incident. In this article, we argue that lean thinking has penetrated texts and literacy practices of two considerably different workplaces, and this has a large impact on the way workers are instructed to think and act with regard to problem handling techniques.